2018
DOI: 10.1101/424408
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of HSV-1 strains circulating in Finland demonstrates the uncoupling of whole-genome relatedness and phenotypic outcomes of viral infection

Abstract: 40A majority of adults in Finland are seropositive carriers of herpes simplex viruses (HSV). 41 Infection occurs at epithelial or mucosal surfaces, after which virions enter innervating nerve 42 endings, eventually establishing lifelong infection in neurons of the sensory or autonomic 43 nervous system. Recent data have highlighted the genetic diversity of HSV-1 strains, and 44 demonstrated apparent geographic patterns in strain similarity. Though multiple HSV-1 genomes 45 have been sequenced from Europe to da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Moreover, given that transgenic s17 also fails to spread extracellularly, it follows that any viruses built in to this backbone are also likely to have this release phenotype. should be noted that recent studies on ten random clinical HSV1 strains isolated in Finland indicated that while these viruses replicated with lower efficiencies than strain 17 syn+ in all cell types tested, and therefore also released fewer virions, the overall proportion of released virus was similar and in some cases higher than strain 17 syn+ [33]. While the nature of the assays carried out in those studies was different to our own (high multiplicity versus spread at low multiplicity respectively), further studies will be required to determine the relationship between efficient virus release and propagation in cell culture.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, given that transgenic s17 also fails to spread extracellularly, it follows that any viruses built in to this backbone are also likely to have this release phenotype. should be noted that recent studies on ten random clinical HSV1 strains isolated in Finland indicated that while these viruses replicated with lower efficiencies than strain 17 syn+ in all cell types tested, and therefore also released fewer virions, the overall proportion of released virus was similar and in some cases higher than strain 17 syn+ [33]. While the nature of the assays carried out in those studies was different to our own (high multiplicity versus spread at low multiplicity respectively), further studies will be required to determine the relationship between efficient virus release and propagation in cell culture.…”
Section: Resultsmentioning
confidence: 82%
“…Such analyses do not prove that either or both of these variations are responsible for the defective release phenotype of these viruses, but it is interesting to note that UL26 encodes a protease which although characterized to be involved in capsid assembly, may nonetheless has the potential to have other activities during infection such as facilitating virus release from the cell surface. Although it has not yet been possible to directly correlate intrastrain genetic changes with phenotypic changes in these viruses, it should be noted that a recent study of clinical isolates also failed to identify sequences that would be predictive for phenotypic differences of virus replication and release [33], suggesting that these phenotypes are complex and multifactorial.…”
Section: Resultsmentioning
confidence: 99%
“…These and other circulating HSV-1 strains have numerous genetic differences [83][84][85], which have been proposed to impact observed phenotypic differences in HSV pathogenesis [86][87][88] and spread [89]. Many TUs containing HSV-1 glycoprotein transcripts (e.g., US5, US6, US7, US8, and UL44) demonstrated higher expression in F-and McKrae-infected neurons versus KOS-infected neurons (Figs 3B and 4).…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Minor variants (MVs) within each genome were detected using VarScan 2.4.2 [60], in a similar manner as previously described [11,12,61]. We used parameters intended to eliminate sequencing-induced errors from the initial calling of MVs.…”
Section: Methodsmentioning
confidence: 99%